2016
DOI: 10.1523/jneurosci.1915-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Target-Dependent Compartmentalization of the Corelease of Glutamate and GABA from the Mossy Fibers

Abstract: The mossy fibers (MFs) corelease glutamate and GABA onto pyramidal cells of CA3 during development, until the end of the third postnatal week. However, the major target cells of the MF are the interneurons of CA3. Therefore, it has been shown that the interneurons of the hilus and stratum lucidum receive this dual monosynaptic input on MF stimulation. Because the plasticity of glutamatergic transmission from the different terminals of the MF is target specific, we here asked whether the corelease of glutamate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
(7 reference statements)
1
14
0
Order By: Relevance
“…Interestingly, we also found that spinal cord neurons exhibit extensive co-expression of glutamate and GABA -two neurotransmitters with opposing functions. Although we did not investigate the release of these transmitters in this work, the possible co-release of glutamate and GABA from single nerve terminals in the brain has been demonstrated extensively ( Beltrán and Gutiérrez, 2012;Galván and Gutiérrez, 2017;Noh et al, 2010;Root et al, 2014;Shabel et al, 2014;Yoo et al, 2016). Our findings support the existence of multitransmitter neurons in the zebrafish spinal cord, as was already established in the lamprey spinal cord (Fernández-López et al, 2012) and the mammalian brain (Granger et al, 2017;Tritsch et al, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, we also found that spinal cord neurons exhibit extensive co-expression of glutamate and GABA -two neurotransmitters with opposing functions. Although we did not investigate the release of these transmitters in this work, the possible co-release of glutamate and GABA from single nerve terminals in the brain has been demonstrated extensively ( Beltrán and Gutiérrez, 2012;Galván and Gutiérrez, 2017;Noh et al, 2010;Root et al, 2014;Shabel et al, 2014;Yoo et al, 2016). Our findings support the existence of multitransmitter neurons in the zebrafish spinal cord, as was already established in the lamprey spinal cord (Fernández-López et al, 2012) and the mammalian brain (Granger et al, 2017;Tritsch et al, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, we also found that spinal cord neurons exhibit extensive co-expression of glutamate and GABA, two neurotransmitters with opposing functions. Although we did not investigate the release of these transmitters in this work, the possible co-release of glutamate and GABA from single nerve terminals in the brain has been demonstrated extensively (Beltrán and Gutiérrez, 2012, Galván and Gutiérrez, 2017, Noh et al., 2010, Root et al., 2014, Shabel et al., 2014, Yoo et al., 2016). Our findings support the existence of multi-transmitter neurons in the zebrafish spinal cord, as was already established in the lamprey spinal cord (Fernández-López et al., 2012) and the mammalian brain (Granger et al., 2017, Tritsch et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In most of cases, synaptic efficacy among boutons issued from a single axon varies with the identity of the postsynaptic cell (Blackman et al, 2013; Markram et al, 1998). Target-cell-dependent heterogeneity relies on differences in the probability of release (Koester and Johnston, 2005), responsiveness to neuromodulators (Buchanan et al, 2012; Delaney and Jahr, 2002; Pelkey et al, 2006; Scanziani et al, 1998) or the ability to co-release GABA and glutamate (Galván and Gutiérrez, 2017). Target-cell-dependent STP has also been described at cerebellar GC-MLI synapses by using stimulation of beam of PFs or clusters of GC somata; upon high-frequency stimulation, compound synaptic responses exhibit a facilitating profile at GC-SC synapses whereas these responses depress at GC-BC synapses (Bao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%